Development of Educational Game to Practice Number Sense Based on Android: Pengembangan Game Edukasi Untuk Melatih Number Sense Berbasis Android - Aminah, Siti; Tanuwijaya, Daniel Eko Prasetyo; Aditya, Addin (Procedia of Social Sciences and Humanities, 2022)
Children have difficulties in learning mathematics because they are still memorizing,they haven’t used their number sense abilities. Number sense is an ability that developed properly and correctly can support logical intelligence in the field of mathematics, especially in numbers. From previous research on number sense, the media for practicing number sense skills still uses paper and writing utensils. In this study, we will develop media to train number sense through android media that can be accessed anywhere, so that it can make it easier for users. The development of this media is in the form of games developed with unity with waterfall stages. The results of the test, the application did not experience errors due to bugs and the test results on several children got good scores.